Stres akademik dan frekuensi konsumsi kopi dengan hiperkolesterolemia pada mahasiswa gizi - Siahaan, Ruth Elisa Putri; Mayasari, Noor Rohmah; Ismawati, Rita; Sholihah, Lini Anisfatus (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2025)
Academic stress and coffee consumption frequency with hypercholesterolemia among nutrition studentsBackground: Hypercholesterolemia is a condition where total blood cholesterol exceeds 200 mg/dL, caused by diet, lack of physical activity, environmental factors, and stress. Objective: This study aimed to investigate the relationships among academic stress, coffee consumption frequency, and hypercholesterolemia among nutrition students. Methods: This cross-sectional study was conducted from April 2024 to February 2025 at Universitas Negeri Surabaya. A total of 92 undergraduate students from the Nutrition Study Program, classes of 2021, 2022, and 2023, were selected using proportional random sampling. Data collection was conducted through interviews using the Perceived Sources of Academic Stress (PASS) questionnaire and the Food Frequency Questionnaire (FFQ), along with cholesterol level measurements obtained via fingertip blood tests. Data were analyzed using the Chi-Square test and Fisher’s Exact Test with a 95% confidence level and a significance level of p<0.05.Results: Most respondents experienced high academic stress (87%), rarely consumed coffee (76%), and had hypercholesterolemia (59%). Statistical analysis showed no significant relationship between academic stress and hypercholesterolemia (p = 0.978), and no significant relationship between coffee consumption frequency and hypercholesterolemia (p = 0.589). Conclusions: There is no significant association between academic stress or coffee consumption frequency and hypercholesterolemia among nutrition students.